The S.O.H.A. project: An open science project from the South - Hachani, Samir (Septentrio Conference Series, 2018)
Our presentation aims to show an original facet of open science: a project from the Souths and for the Souths. In S.O.H.A (Science Ouverte Haiti Afrique), we use Souths in plural because we believe in a plurality of layers of development. Our project aims to showcase Souths' research in indigenous languages, in local settings and in subjects that are of interest to the indigenous people. We will present the different program and tutorials in the project to prove that an open science from the Souths and for the Souths is possible.